The Use of Ethnomathematics Learning Media Based on Augmented Reality for Madrasah Students - Ahmad Anis Abdullah; R Richardo; T Rochmadi; A Wijaya; Nurkhamid Nurkhamid (STAI Hubbulwathan Duri, 2022)
This study presents Augmented Reality (AR) implementation for learning geometry mathematics with a cultural approach in junior high schools. The research method used was ADDIE (analysis, design, development, implementation, and evaluation) by limiting it to (1) exploration analysis, (2) design, (3) development, and (4) implementation. Applying the AR concept to the mathematics learning method with a cultural approach is hoped to create an interesting and fun mathematics learning atmosphere. This is because the application of AR concepts in mathematics learning can help students towards abstract mathematical concepts with the help of 3D objects and improvisation of appropriate sounds and images. The research results are an AR application prototype for learning geometric mathematics with a cultural approach in junior high schools, which can be used for geometry material in junior high schools for both classroom and online learning.